Strain Mechanisms in Lead-Free Ferroelectrics for Actuators - Acosta, Matias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book addresses and analyzes the mechanisms responsible for functionality of two technologically relevant materials, giving emphasis on the relationship between structural transitions and electromechanical properties. The author investigates the atomic crystal structure and microstructure by means of thermal analysis, as well as diffraction and microscopy techniques. Electric field-, temperature- and frequency-dependent electromechanical properties are also described. Apart from this correlation between structure and properties, characterization was also performed to bridge between basic research and optimization of application-oriented parameters required for technological implementation. The author proposes guidelines to the reader in order to engineer functional properties in other piezoelectric systems, as well as in other similar functional materials with the perovskite structure.
Introduction -- Theoretical -- Literature Review: Piezoceramics for Actuator Applications -- Experimental Procedure -- Results and Discussions.
Keywords: Ceramic materials; Materials -- Analysis; Spectrum analysis; Ceramics; Characterization and Analytical Technique; Spectroscopy